A contextual ICT model to explain adoption of mobile applications in developing countries: A case study of Tunisia - Dhehibi, Boubaker; Dhraief, Mohamed Zied; Frija, Aymen; Ouerghemmi, Hassen; Rischkowsky, Barbara; Rudiger, Udo (Public Library of Science, 2023)
In Tunisia, agriculture is the main source of livelihood for more than 75% of small and sub sistence farmers with minimal use of technology. The use of information and communication technology (ICT),such as mobile applications, represents a pertinent opportunity for these smallholders to access agricultural innovation and market information and improve their farming technologies and farm management. Thus, ICT can act as a replacement to foster access to innovation for this category of farmers. Unfortunately, the underuse of mobile applications has contributed to low and slow adoption of agricultural innovation and conse quently the benefits of this technology have not been attained. The purpose of this study is to identify the factors affecting the adoption of Short Message Service (SMS) through a con textual ICT model for livestock, olive crop, and beekeeping. Data were collected from 200 small-scale beekeepers, 225 olive growers, and 140 livestock breeders selected in Jen douba, Kairouan, and Zaghouan in Tunisia. The objective of this paper is to examine the fac tors that influence mobile applications using the partial least squares structural equation modelling technique, for livestock, olive crop, and beekeeping agricultural activities. The results showed that the final ICT-induced structural models were highly predictive of the use of SMS and its increased adoption. Factors affecting the use of SMS differed according to the farming system. The major perceived factor affecting the use of SMS was ‘observability’ for livestock farmers, ‘compatibility’ for olive growers, and ‘information quality’ for beekeepers. Understanding these factors by taking into account the specificity of the agricultural activity leads to a better understanding of the adoption of ICT tools by smallholder farmers in Tunisia